(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: Bispectral index (BIS) monitoring may assist reduction in utilisation of anaesthetic agentsduring cardiac surgical procedures. This study was designed to test whether the use of BIS monitoringreduces the anaesthetic requirements during on-pump coronary artery bypass grafting (CABG). Methods: This prospective observational randomized study was conducted in the department ofcardiothoracic vascular anaesthesia and critical care of Apollo Hospitals,Dhaka on 35 patients undergoingelective CABG. The following patients were excluded from the study; patient with cerebrovascular accident(CVA), excessive alcohol intake and drug abuse. Results: The mean heart rate and CVP were statistically significant (p<0.05) when compared start atsurgery vs different follow up, however mean MAP was significantly reduced when compared start atsurgery vs different follow up. At induction mean BIS was 59.08±12.40%, at onset of CBP mean BIS was27.43±13.51% and at end of anaesthesia mean BIS was 85.62±12.83%. Mean BIS was significantlydecreased when compared induction vs onset of CBP. However, mean BIS was significantly increasedwhen compared induction vs end of anaesthesia. Conclusion: Anesthesia maintained by bispectral index monitoring reduces the incidence ofhaemodynamic unstability and facilitates titration of anesthetic agents during cardiopulmonary bypassand thus may assist recovery from anesthesia. JBSA 2019; 32(2): 27-31